Spermine Confers Stress Resilience by Modulating Abscisic Acid Biosynthesis and Stress Responses in Arabidopsis Plants - Marco, Francisco; Busó, Enrique; Lafuente, Teresa; Carrasco, Pedro (Frontiers in Plant Science, 2019)
Polyamines (PA) constitute a group of low molecular weight aliphatic amines that have been implicated as key players in growth and development processes, as well as in the response to biotic and abiotic stresses. Transgenic plants overexpressing PA-biosynthetic genes show increased tolerance to abiotic stress. Therein, abscisic acid (ABA) is the hormone involved in plant responses to environmental stresses such as drought or high salinity. An increase in the level of free spermine (Spm) in transgenic Arabidopsis plants resulted in increased levels of endogenous ABA and promoted, in a Spm-dependent way, transcription of different ABA inducible genes. This phenotype was only partially reversed by blocking ABA biosynthesis, indicating an ABA independent response mediated by Spm. Moreover, the phenotype was reproduced by adding Spm to Col0 wild-type Arabidopsis plants. In contrast, Spm-deficient mutants showed a lower tolerance to salt stress. These results indicate that Spm plays a key role in modulating plant stress responses